FACTORS INFLUENCING MALE INVOLVEMENT IN SAFE MOTHERHOOD AMONG COMMUNITIES IN KWALE AND KILIFI IN COASTAL KENYA - Ouma, George; Karanja, Prof. Simon; Udu, Dr.Rahma (Global Journal of Health Sciences, 2018)
Purpose: The main purpose of the study was to determine the factors influencing male involvement in safe motherhood among communities of Kwale and Kilifi Counties of Coastal Kenya. Materials and methods: The study was descriptive cross sectional design. The study focused on women of child-bearing age 15 - 49 and men aged 15 - 54 from Kilifi and Kwale counties in 14 health facilities. Qualitative and quantitative methods of data collection were used. Interviewer-administered questionnaire were administered to women who were attending ANC. Data was also collected using semi-structured interviews with health service providers, community leaders and county directors. Focus group discussions were conducted using FGD guide with four women and men groups. Analysis was done using SPSS and NVivo softwares. Results: The findings of the study revealed that Men and women interviewed in the two rural counties believed safe motherhood practices especially in pregnancy and childbirth are a preserve of women. Illiteracy, sociocultural factors, weak health systems and economic factors were found to be the major barriers to male involvement. Traditional gender roles defined the involvement of men mostly perceived to be provision of funds for transport and food. Unique Contribution to Theory, Practice and Policy: This study recommended a defined program that target male involvement strategy. It will involve male champions/men ambassador/agents being supported to go to the Mnazi dens and educate, sensitize and support dialogues with men aged 35 years and below. A targeted alcohol abuse sensitization and education will go a long way. A friendly health system be put in place to accommodate men. Friendlier timing including weekends and late hours, space at the clinics to accommodate men and responsive health workers.